The university’s role in coastal resources management for achieving sustainable development - Rusman Ghazali, TB. Massa Djafar,; Saputra, Jumadil; Dewi, Risna; Muhammad, Zikri (Opción, 2020)
This study aims to investigate the role of the university in achieving sustainable development explicitly relating coastal resources management via a qualitative approach and document analysis. As a result, to budget support from the central government to improve higher education, the local government has to make a policy to strengthen the role of universities in the local area, especially in the research area to develop an excellence center. In conclusion, the university must be an active and intensive development actor to help solve the problems of development and to improve the welfare of the community.